Novel 3D human trophoblast culture to explore T. cruzi infection in the placenta - Apodaca, Sofia; Di Salvatore, Marco; Muñoz-Calderón, Arturo; Curto, María de los Ángeles; Longhi, Silvia A.; Schijman, Alejandro G. (Frontiers in Cellular and Infection Microbiology, 2024)
IntroductionHuman trophoblastic cell lines, such as BeWo, are commonly used in 2D models to study placental Trypanosoma cruzi infections. However, these models do not accurately represent natural infections. Three-dimensional (3D) microtissue cultures offer a more physiologically relevant in vitro model, mimicking tissue microarchitecture and providing an environment closer to natural infections. These 3D cultures exhibit functions such as cell proliferation, differentiation, morphogenesis, and gene expression that resemble in vivo conditions.MethodsWe developed a 3D culture model using the human trophoblastic cell line BeWo and nonadherent agarose molds from the MicroTissues® 3D Petri Dish® system. Both small (12–256) and large (12–81) models were tested with varying initial cell numbers. We measured the diameter of the 3D cultures and evaluated cell viability using Trypan Blue dye. Trophoblast functionality was assessed by measuring β-hCG production via ELISA. Cell fusion was evaluated using confocal microscopy, with Phalloidin or ZO-1 marking cell edges and DAPI staining nuclei. T. cruzi infection was assessed by microscopy and quantitative PCR, targeting the EF1-α gene for T. cruzi and GAPDH for BeWo cells, using three parasite strains: VD (isolated from a congenital Chagas disease infant and classified as Tc VI), and K98 and Pan4 (unrelated to congenital infection and classified as Tc I).ResultsSeeding 1000 BeWo cells per microwell in the large model resulted in comparable cellular viability to 2D cultures, with a theoretical diameter of 408.68 ± 12.65 μm observed at 5 days. Functionality, assessed through β-hCG production, exceeded levels in 2D cultures at both 3 and 5 days. T. cruzi infection was confirmed by qPCR and microscopy, showing parasite presence inside the cells for all three tested strains. The distribution and progression of the infection varied with each strain.DiscussionThis innovative 3D model offers a simple yet effective approach for generating viable and functional cultures susceptible to T. cruzi infection, presenting significant potential for studying the placental microenvironment.